A propósito de la sentencia «coram» Pinto de 26 de marzo de 1999 Notas sobre la responsabilidad contractual y la responsabilidad aquiliana en Derecho canónico - Viejo-Ximénez, José Miguel; Quintana-Afonso, Amado (2023)
The coram Pinto Judgment (26 March 1999) enables an exploration, from a historical perspective, of the scope and meaning of the canonization of civil law in relation to obligations and liability. The canonization of civil laws concerning compensation for damages is supported by the canonical tradition. The sources of c. 128 CIC 83 are not to be found in CIC 17, but in the chapters of the title De (iniuris et) damno dato of the ius novum, as well as in the rules of the ius romanum which the Decretalists used to interpret this rubric in a systematic way.
Keywords: Canonización de leyes civiles; Decretalistas; Derecho de decretales; Derecho romano; Responsabilidad aquiliana; Responsabilidad contractual